The Veil in the Abrahamic Faiths: A Cross-National Analysis - Moaddel, Mansoor (Journal for the scientific study of religion, 2026)
Explanations for veiling among Muslim women fall into two main clusters of ethnographic studies. The first, from the 1990s, sees veiling as an accommodation strategy through which women navigate tensions between autonomy and patriarchy or subvert such norms to cultivate piety—though the evidence still reflects fundamentalism's influence. The second, emerging after the 2011 Arab Spring, focuses on women doffing the veil. Viewed together, the two reflect the spirit of their times: veiling aligned with the rise of fundamentalism, unveiling with its decline. Using a clash-of-values framework, this paper analyzes data from 10 Middle Eastern countries and among adherents of the Abrahamic faiths. Findings show veiling preference skews more conservative in fundamentalist contexts, while liberal ones support more relaxed dress codes. Sartorial conservatism weakens with greater female employment and social media access, but strengthens in countries with more men and younger populations. At the individual level, conservative veiling correlates with stronger fundamentalist orientation, religiosity, and support for gender segregation, but weakens among those committed to liberal values or with higher socioeconomic status. Since clothing projects power, future research should examine how the nature of political power mediates religion–clothing dynamics.